Constructing hierarchical sulfur-doped nitrogenous carbon nanosheets for sodium-ion storage. (10th October 2017) - Chen, Kejun; Hou, Hongshuai; Huang, Caijin; Ji, Xiaobo; Qiu, Xiaoqing
Abstract: Hierarchical sulfur-doped nitrogenous carbon (S/NC) and nitrogenous carbon (NC) nanosheets are successfully fabricated by carbonization of their corresponding precursor polymers which are synthesized through the polymerization reaction of dianhydride and multi-amine compounds. Hierarchical S/NC nanosheets deliver greatly enhanced reversible capacity, compared with hierarchical NC nanosheets, of 280 mAh g −1 at a current density of 100 mA g −1 after 300 cycles. It is found that the introduction of sulfur species in carbon skeleton results in increasing the turbostratic structures, rather than enlarging the interlayer distances, for boosting the specific capacity of sodium-ion storage. The turbostratic structures and sulfur dopant existed in the carbon can offer more active sites for the sodium-ion storage. Carbon-based materials doped with sulfur are capable of improving the sodium-ion storage property, which can broaden the horizon of designing a string of outstanding carbon materials for the future energy storage technologies.